2005
DOI: 10.3959/1536-1098-61.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Response of Decadal Variability in Larch Tree-Ring Chronologies from Upper Tree-Lines of the Russian Altai

Abstract: We developed a network of tree-ring width chronologies of larch (Larix sibirica Led.) from upper tree-lines of the southeast Altai Mountains, South Siberia. Annual tree-ring variability of chronologies since A.D. 1710 was compared using factor analysis. The factor analysis clustered eight tree-ring chronologies into two groups that were used for compositing chronologies. One resulting composite chronology (A.D. 1582-1994) averaged sites from upper tree-lines in glacier-free areas and another chronology (A.D.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Since then, many dendroclimatological studies have been performed in the western , middle (Sidorova et al, 2012), and eastern (Davi et al, 2009) Altai Mountains. Most of these studies have focused on the development of tree-ring chronologies and the response of tree growth to climate (Panyushkina et al, 2005;Zhang et al, 2007;Shang et al, 2010a;Hu et al, 2011;Li et al, 2011;Myglana et al, 2012;Chen et al, 2012a). However, these studies have primarily concentrated on reconstruction of the local paleoclimate (Zhang et al, 2008;Shang et al, 2010bShang et al, , 2011Hu et al, 2012a).…”
Section: Methodsmentioning
confidence: 95%
“…Since then, many dendroclimatological studies have been performed in the western , middle (Sidorova et al, 2012), and eastern (Davi et al, 2009) Altai Mountains. Most of these studies have focused on the development of tree-ring chronologies and the response of tree growth to climate (Panyushkina et al, 2005;Zhang et al, 2007;Shang et al, 2010a;Hu et al, 2011;Li et al, 2011;Myglana et al, 2012;Chen et al, 2012a). However, these studies have primarily concentrated on reconstruction of the local paleoclimate (Zhang et al, 2008;Shang et al, 2010bShang et al, , 2011Hu et al, 2012a).…”
Section: Methodsmentioning
confidence: 95%
“…Similar to precipitation, a positive effect was found for the response of dominant height to temperature. Although temperature is also a key factor in forest growth [48,49], the correlation between temperature and forest growth was inconsistent in previous studies, even for larch in China. Shen et al [30] found an opposite result to the present study, i.e., that temperature showed a negative effect on site index of Larix olgensis in Jilin, China.…”
Section: Climate-sensitive Dominant Height Growth Modelmentioning
confidence: 94%
“…Several 14 C dates were developed to control overlaps between tree-ring width chronologies of tombs and sites. A 1586-yr tree-ring width chronology of larch (AD 420-2005) from 10 upper tree-line sites of southeastern Altai was used as a reference curve for tree-ring crossdating where possible (extended tree-ring chronology from Panyushkina et al [2005]). …”
Section: Methodsmentioning
confidence: 99%